Community policing in Small City, Iowa - Pino, Nathan (1999)
The purpose of this study was to evaluate community policing in Small City, Iowa from the point of view of the citizenry and the police. There were four objectives in the study: (1) To examine the extent to which the COP philosophy is being implemented in Small City, (2) To see if COP is working in the minds of both the citizens and police officers, (3) To examine what influences citizen attitudes toward the police in general, and (4) To see if citizens view any additional benefits to COP (increased social capital and increased community involvement in areas besides crime reduction) besides COP's traditional benefits (crime and fear reduction). A variety of methods were utilized to meet the above objectives, including focus groups with neighborhood group members, interviews with police officers and a city official, and a mail survey of the general population of Small City. This study also utilized the criminal events perspective and the concept of social capital. Results show that COP in Small City is an addition to the existing structure rather than a city and department-wide Philosophy; This has been exacerbated because the police department is under-funded and under-staffed, causing inter-departmental political turmoil. Because of these problems the experiences of respondents with COP have not always been positive. Attitudes toward the police in general are largely determined by actual contact with the police, perceptions of fear and perceptions of neighborhood livability, and contextual factors such as age, sex, race, and home ownership status. It is possible that COP could work in Small City because of neighborhood organizing and other network building between neighborhood groups and public agencies, increased social capital within and between neighborhood groups and public agencies other than the police department, and overwhelming citizen support for COP. However, there are many barriers preventing such success. These barriers include small levels of consistent citizen involvement, a lack of all neighborhoods being organized, a lack of resources for the police which causes animosity among officers and other inter-organizational problems, and a lack of genuine communication and trust between the citizenry and the police